Small volatile lipophilic molecules induced belowground by aphid attack elicit a defensive response in neighbouring un-infested plants - Cascone, Pasquale; Vuts, Jozsef; Birkett, Michael A.; Rasmann, Sergio; Pickett, John A.; Guerrieri, Emilio (Frontiers in Plant Science, 2023)
In pioneering studies on plant-aphid interactions, we have observed that Vicia faba plants infested by aphids can transmit signals via the rhizosphere that induce aboveground defence in intact, neighbouring plants. The aphid parasitoid Aphidius ervi is significantly attracted towards intact broad bean plants grown in a hydroponic solution previously harbouring Acyrtosiphon pisum-infested plants. To identify the rhizosphere signal(s) possibly mediating this belowground plant-plant communication, root exudates were collected using Solid-Phase Extraction (SPE) from 10-day old A. pisum-infested and un-infested Vicia faba plants hydroponically grown. To verify the ability of these root exudates to trigger defence mechanisms against the aphids we added them to V. fabae plants grown in hydroponic solution, and tested these plants in the wind-tunnel bioassay to assess their attractiveness towards the aphids’ parasitoids A. ervi. We identified three small volatile lipophilic molecules as plant defence elicitors: 1-octen-3-ol, sulcatone and sulcatol, in SPE extracts of A. pisum-infested broad bean plants. In wind tunnel assays, we recorded a significant increase in the attractiveness towards A. ervi of V. faba plants grown in hydroponic solution treated with these compounds, compared to plants grown in hydroponic treated with ethanol (control). Both 1-octen-3-ol and sulcatol have asymmetrically substituted carbon atoms at positions 3 and 2, respectively. Hence, we tested both their enantiomers alone or in mixture. We highlighted a synergistic effect on the level of attractiveness towards the parasitoid when testing the three compounds together in respect to the response recorded against them singly tested. These behavioural responses were supported by the characterization of headspace volatiles released by tested plants. These results shed new light on the mechanisms underlying plant-plant communication belowground and prompt the use of bio-derived semiochemicals for a sustainable protection of agricultural crops.